Perception of physical exercise in Turkish pregnant women and affecting factors - BİLGİN, ZÜMRÜT (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Objective: This study investigated perceptions of physical exercise in Turkish pregnant women and affecting factors. Methods: This descriptive study was conducted between 15 May 2016 and 30 December 2016 at a maternity hospital in Istanbul, Turkey. The sample consisted of 331 pregnant women who agreed to participate in the study. A Questionnaire Form and the Exercise Benefit and Obstacle Scale were used to collect the data of the study. Results: The mean age of the participants was 29.18 +/- 7.02 years. The body mass index of 13% of the pregnant women was >= 30, and 19.3% of them gained >= 14 kg during their pregnancy. In the study, 27.8% of the pregnant women were found to be walking as exercise. The first three factors that prevented exercise during pregnancy were the distance of exercise facilities (60.4%), that the programmes in the facilities were not suitable for pregnant women (56.5%) and the insufficient number of exercise facilities (55.3%). The relationship between the women's pre-pregnancy sports experiences, exercise during pregnancy, distance of exercise facilities and insufficient number of exercise facilities and their mean exercise obstacle score was significant (p<.05). Conclusion: In the study, a small number of pregnant women walked as an exercise. It is recommended to expand exercise facilities and create exercise programmes for pregnant women.
Keywords: Exercise benefits; exercise obstacle; effective factors; pregnancy; physical activity; GESTATIONAL WEIGHT-GAIN; PERCEIVED BARRIERS; BENEFITS; FACILITATORS; METAANALYSIS; PREVALENCE